(untitled) (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
An increase in blood cholesterol levels is one of the triggers for atherosclerosis. The use of natural components, such as avocado fruit juice, is an alternative to lowering cholesterol levels. Avocados contain hypolipidemic agents such as beta-sitosterol, omega-9, oleic acid, pantothenic acid (vitamin B5), niacin (vitamin B3), vitamins A, C, and E, cysteine amino acid, selenium, and fruit fiber. The study’s goal was to examine the potential effects of providing avocado juice on cholesterol levels. The pretest-posttest design with a control group is used in this type of experimental research. The research sample consisted of 36 male white rats aged 2-3 months which were divided into 3 normal, positive, and negative control groups, and 3 treatment groups with avocado juice doses of 3.5mL, 4mL, and 4.5mL. The research phase involved acclimatization and generation of hypercholesterolemic rats by inducing quail egg yolk orally and assessing the effectiveness of avocado juice orally once a day for 7 days. Cholesterol levels were tested three times: after acclimation, induction by oral quail egg yolk, and administration of avocado juice. After egg yolk induction, the average cholesterol level in all treatment groups was 139.1 mgdL-1, 164.5 mgdL-1, and 190.1 mgdL-1, respectively. Following the administration of avocado juice, there was a decrease in all treatment groups with mean cholesterol levels of P1, P2, and P3, or 68.7 mgdL-1, 64.1 mgdL-1, and 42 mgdL-1. These findings are supported by test results from One Way Anova, which showed that after the administration of avocado juice, there were variations in cholesterol levels between groups. The study’s finding is that consuming avocado juice can lower cholesterol levels.